the Dampak Pergaulan Bebas Terhadap Perilaku Remaja di SMA Negeri 3 Cimahi: Pergaulan bebas Terhadap Perilaku Remaja - suwandana, Aldy Noor Chalik; Yuningsih, Yuyun (Indonesian Journal of Social Work, 2024)
This research is entitled "The Impact of Promiscuity on Adolescent Behavior at SMA Negeri 3 Cimahi". Promiscuity is a social phenomenon that is often associated with behavior that is not in accordance with the norms and values ​​that apply in society. This phenomenon can have negative impacts on individuals and communities, including increased physical and mental health risks, as well as the breakdown of social and family relationships. Teenagers are unstable individuals whose emotions are vulnerable to being uncontrolled by youthful self-control. Behavior is any form of activity carried out by individuals, organizations, or other living creatures that can be observed and measured. This includes any action, response, or reaction that can be noticed and assessed by other people or by certain measuring devices. Behavior can be influenced by a variety of factors, including the environment, culture, values, and individual experiences. The aim of this research is to ensure that today's teenagers are more focused in their relationships, namely by carrying out positive and useful activities for themselves, their families and the surrounding community, also so that teenagers do not get caught up in promiscuity, describe supporting and inhibiting factors, and describe practical and theoretical implications. The method used is a qualitative approach and informant selection techniques using the case study method. There are several data collection techniques used, namely 1) Observation, 2) In-depth interviews, 3) Document study. The number of informants is 3 main informants and 1 supporting informant. As a result of this research, researchers found information that the impact of promiscuity is 3 negative activities, namely 1) Alcohol consumption, 2) Drug abuse, and 3) Free sex. There are several factors driving promiscuity, namely, lack of family communication, disharmonious family (Broken Home), peer influence and identity crisis. Keywords : Promiscuity, Behavior, Teenagers